- Analisis Komparatif Trading Volume Activity, Abnormal Return, dan Bid-Ask Spread Sebelum dan Sesudah Stock Split pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021: - - Hadi Lukito; Damayanti Damayanti (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
This research is an event study that aims to prove the reaction of the Indonesian capital market to stock split in companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This study uses secondary data sources obtained from websites the Indonesian Stock Exchange and Yahoo Finance. The event observation period is 20 days which is divided into 10 days (h-10) before, event day (h-0), and 10 days (h+10) after the stock split. Data analysis technique used paired sample t-test and Wilcoxon signed rank test. The results showed that 1) there was no significant difference in trading volume activity before and after the stock split 2) there was a significant difference in abnormal returns before and after the stock split and 3) there was no significant difference in the bid-ask spread before and after the stock split. Thus the stock split has information content that causes the capital market to react.